Commentary: an eye on PET quantification. - Walker, Matthew D; Sossi, Vesna (Molecular Imaging & Biology, 2015)
Positron emission tomography (PET) is generally considered to be a quantitative imaging modality, allowing assessment of regional differences in radiotracer accumulation and the derivation of quantitative physiological information. Due to the increasing complexity of PET technology, the quantitative accuracy of PET images has to be continually reassessed if PET is to maintain its quantitative reputation. In this commentary, we discuss the results from a recent inter-scanner study in which the quantitative outcome measures from human studies were compared for three different radiotracers. The approach is a useful complement to standard phantom tests such as those prescribed by NEMA, but the resulting data are more difficult to interpret.